SKRINING ENZIM DARI SAMPEL DAUN JELUTUNG RAWA (Dyera lowii Hook f.) UNTUK ANALISIS ISOZIM SEBAGAI STUDI AWAL KERAGAMAN GENETIK (Screening Enzyme from Leaf of Dyera lowii Hook f. to Isozyme Analysis. The First Study of Genetics Variety) : Tri Suwarni Wahyudiningsih - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACT Jelutung rawa (Dyera lowii Hook f.) is the commercial and endemic species of peat-swamp forest with sensitive status, therefore the research to analyze its genetics variety is very important. The research was aimed to analyze the seven of enzyme in the leaf of D. lowii that well-marked by the emergence of polymorphic tape pattern consistently. The research was conducted at November to December 2012 in the tree improvement laboratory of Gadjah Mada University. Leaf of D. lowii samples were gotten from D. lowii plantation at the Cilik Riwut Street, nine km from Palangka Raya City. There are seven enzyme system to screening, namely Shikimate Dehydrogenase (SHD; EC 1.1.1.25), NAD(P)H-Diaphorase (DIA; EC 1.6.2.2), Glutamate Oxaloacetate Transaminase (GOT: EC 1.11.1.7), Acid Phosphatase (ACP; EC 3.1.3.2), 6-Phosphogluconate Dehydrogenase (6-PG; EC 1.1.1.44), Esterase (EST; EC 3.1.1), dan Peroxidase (POD; EC 1.11.1.7). Stages of research were preparation, leaf extraction, supernatant, electroforesis “Wendel & Weeden”, colouring, fixation, and gel dehydration. Isozyme was detected using Rf (Relative value from Bromophenol Blue) to make the zymogram. Polymorphic tape pattern consistently was resulted by enzymes of DIA, POD, ACP, EST, and GOT, whereas polymorphic tape pattern inconsistently was resulted by enzymes SHD and 6-PG. Furthermore, the polymorphic tape pattern consistently could to analyze genetics variety. The first study of genetics variety showed that there are four locus at the leaf of D.lowii, namely Est-1, Est-2, Est-3, and Got-1 in the 14 of alel. Keywords: Dyera lowii, enzyme, isozyme analysis, polymorphic